2016
DOI: 10.5370/jeet.2016.11.6.1614
|View full text |Cite
|
Sign up to set email alerts
|

United Electromagnetic Characteristics and Online Monitoring Method of Static Air-gap Eccentricity of Turbo-Generator

Abstract: -The purpose of this paper is to investigate the united Electromagnetic characteristics for the effective monitoring on the static air-gap eccentricity (SAGE) of turbo-generator. Different from other studies, this paper not only studies on the unbalanced magnetic pull (UMP) and the vibration characteristics of the stator and the rotor, but also investigates the harmonic features of the magnetic flux density and the circulating current inside the parallel branches (CCPB). The theoretical calculation, together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For SAGE, scholars have investigated both the mechanical and the electrical faulty properties. For instance, He et al investigated the unbalanced magnetic pull (UMP) [8], the vibration characteristics of the rotor [9], and the circulating current inside the parallel branches [10]. Besides the mechanical characteristics, it is also found that the stator phase current is an effective tool to identify the broken magnet and SAGE in permanent magnet synchronous motors [11], while at the same time, the shaft voltage measurements have been found as a better means for the optimal measurement modality that leads to a minimal identification error of SAGE in synchronous machines [12].…”
Section: Introductionmentioning
confidence: 99%
“…For SAGE, scholars have investigated both the mechanical and the electrical faulty properties. For instance, He et al investigated the unbalanced magnetic pull (UMP) [8], the vibration characteristics of the rotor [9], and the circulating current inside the parallel branches [10]. Besides the mechanical characteristics, it is also found that the stator phase current is an effective tool to identify the broken magnet and SAGE in permanent magnet synchronous motors [11], while at the same time, the shaft voltage measurements have been found as a better means for the optimal measurement modality that leads to a minimal identification error of SAGE in synchronous machines [12].…”
Section: Introductionmentioning
confidence: 99%
“…The generator is the key equipment for a power plant and needs timely and accurate monitoring and maintaining. Typically, after a long-term operation, generators may endure many electrical faults such as the rotor interturn short circuit (RISC) [1] and the stator interturn short circuit [2,3], as well as mechanical faults such as rotor eccentricity [4].…”
Section: Introductionmentioning
confidence: 99%